HABITUAL USE OF LOCAL LANGUAGE: FACTOR AFFECTING DIFFICULTY IN ACCEPTING ENGLISH AMONG STUDENTS - Elinda Umisara; Irfan Fauzi (STBA Pontianak, 2023)
This study investigated the relationship between habitual use of local language and students' difficulty accepting English. The research was conducted using a qualitative study. The data is collected through survey questionnaires, observation, and focus group discussions. The participants in this study are 78 students from four study programs at Universitas Muhadi Setiabudi. These are Indonesian Language and Literature Education, Primary School Teacher Education, Pharmacy, and Nutrition Study Program at the undergraduate level. The results showed that habitual use of local language significantly affected students' difficulty in accepting and adopting English. The researcher has found that the frequent use of the local language can create a linguistic comfort zone, making it challenging to learn and accept a foreign language like learning English. Ultimately, the success of learning English depends on a variety of factors, including the student's motivation, learning style, and exposure to the language. Furthermore, the student's motivation, learning style, and exposure to the language were also important factors contributing to the resistance towards learning English.